Condrolipoma na orelha de um cão - de Souza, Maria de Fátima; Sarmento, Alinne Emanuelle Monteiro; Barbosa, Francisca Maria Sousa; Siqueira, Raul Antunes Silva; Talieri, Ivia Carmem; Lucena, Ricardo Barbosa (Acta Scientiae Veterinariae, 2017)
Background: Lipoma is defined as a tumor composed of mature adipocytes, identical to the cells that form normal adult fat. Other elements may also be present, such as cartilaginous tissue. Chondrolipoma is characterized by the presence of differentiated cartilage islands spread within a typical lipoma, in which mucin and collagen can be observed around isles of chondrocytes. This condition affects mainly middle-aged or elderly dogs as well as elderly humans. In the scientific literature, chondrolipomas have not yet been described on the ear of dogs. Therefore, this study aimed to report a case of chondrolipoma on the ear of a dog and its histopathological and histochemical description. Case: A female, 10-year-old, Labrador retriever dog was admitted to the Veterinarian Hospital of the Federal University of Paraíba (UFPB), Areia, Brazil. The dog was presented with an ulcerated pendulous nodule on the ear, with a clinical evolution of approximately 7 months. A biopsy sample was taken and submitted to the Veterinary Histopathology Laboratory of the UFPB. Macroscopic evaluation revealed a pendulous and firm nodule, with a round apex, measuring 1.3cm in diameter. The epidermis covering the nodule exhibited an ulcer of 0.5cm in length. The nodule exhibited resistance to cutting and the surface was dark red with hard areas in the center. Sample was fixed in 10% formalin and routinely processed for histology, embedded in paraffin, and stained with hematoxylin and eosin (HE), alcian blue (AB), Masson’s trichrome (MT), and periodic acid-Schiff (PAS). Histopathological evaluation revealed that the nodule was encapsulated, formed by adipocytes of variable sizes. Adipocytes were well-differentiated and the nodule was defined as lipoma. Within the lipoma there was proliferation of chondrocyte islands in a bluish basophilic matrix. Adjacently, abundant fibrous connective tissue was found intertwined with blood vessels. Some vessels exhibited red blood cells in the vicinity, indicating hemorrhage. The epidermis covering the nodule was slightly acanthotic and moderately hyperkeratotic. MT staining marked the fibrous tissue in blue. AB staining revealed blue areas confirming the presence of mucin around cartilage islands. PAS staining revealed the presence of glycogen between mesenchymal cells, which included chondrocytes. Discussion: The diagnosis of chondrolipoma was concluded with the presence of a well-differentiated lipoma, randomly intertwined with cartilage islands, which were also well-differentiated and spread within a typical lipoma. Additionally, the presence of mucin and collagen around the isles of chondrocytes facilitated the diagnosis. Chondrocytes presented different phases of maturation. The case described here exhibited microscopic characteristics that were similar but somewhat different to those previously reported by other authors, in considering that the nodule was encapsulated, and did not exhibit cell atypia or mineralization in the cartilage islands. Most studies published used PAS and Masson’s trichrome staining techniques to confirm the diagnosis of chondrolipoma. However, alcian blue also aids in diagnosing this condition. The tumor developed for months before the dog was taken to a veterinarian, when it finally became ulcerated, which characterized it as non-invasive. Chondrolipoma is a benign tumor, which does not induce metastasis and once excised does not exhibit recurrence. In veterinary medicine, the presence of cartilage within a lipoma is a rare event.